2021
DOI: 10.1097/mop.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mRNA vaccine allergy

Abstract: Purpose of review A known history of a severe allergic reaction (e.g., anaphylaxis) to any component of the vaccine is the only contraindication to coronavirus disease 2019 (COVID-19) mRNA vaccination. It is important for pediatricians to understand the likelihood of an allergic reaction to COVID-19 mRNA vaccines, including its excipients. Recent findings Episodes concerning for anaphylaxis were immediately reported following early administration of COVID-19 mRNA vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Individuals with higher education levels may pay more attention to their physical condition and be more sensitive to adverse reactions [27] . The prevalence (95% CI) of anaphylaxis or hospitalization with the three doses was 0.39% (0.21%–0.66%), 0.24% (0.10%–0.47%), and 0.33% (0.16%–0.59%) in our study, which was similar to previous studies [25] , [28] , [29] . Fever, as a measurable objective indicator, is often a concern after vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with higher education levels may pay more attention to their physical condition and be more sensitive to adverse reactions [27] . The prevalence (95% CI) of anaphylaxis or hospitalization with the three doses was 0.39% (0.21%–0.66%), 0.24% (0.10%–0.47%), and 0.33% (0.16%–0.59%) in our study, which was similar to previous studies [25] , [28] , [29] . Fever, as a measurable objective indicator, is often a concern after vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicate confirmed anaphylaxis caused by COVID-19 vaccines is rare, 15,16 likely because of a lack of preexisting immunoglobulin E antibodies against the novel COVID-19 mRNA vaccine excipient PEG and other vaccine components 17 . Similarly, a cohort study found that 98% of a group of highly allergic individuals had no allergic reaction after COVID immunization, 1% had mild allergic responses, and only 0.7% had anaphylactic reactions 18 …”
Section: Resultsmentioning
confidence: 99%
“…A negative ST does not exclude anaphylaxis, as non-IgE mechanisms such as CAPRA may be implicated. Administration of future vaccines with negative ST warrants consideration of precautions such as administration of antihistamines or incremental or staged doses of the vaccine [ 33 ].…”
Section: Discussionmentioning
confidence: 99%